Replacing protruding domains of MrNV virus-like particles with sialic acid binding domains enhances binding to SARS-CoV-2 susceptible cells and reduces pseudovirus infection - Supawich Boonkua; Orawan Thongsum; Rueangtip Chantunmapitak; Purimpuch Soongnart; Somkid Jaranathummakul; Kitima Srisanga; Patompon Wongtrakoongate; Somluk Asuvapongpatana; Wattana Weerachatyanukul; Atthaboon Watthammawut; Monsicha Somrit (Scientific Reports)
Abstract The SARS-CoV-2 virus continues to pose a public health threat due to its ability to rapidly mutate into multiple variants via mutation in its spike (S1/2) proteins. These mutations can lead to viral variants capable of escaping antibody neutralization. The interaction between the SARS-CoV-2 spike protein and the host ACE2 receptor is influenced by carbohydrate-mediated mechanisms, as the spike is heavily glycosylated with terminal sialic acids, making these sugar moieties attractive targets for therapeutic intervention. We aimed to study the complete replacement of their protrusion domains of Macrobrachium rosenbergii nodavirus capsid protein with the larger ligands in the form of carbohydrate-recognition domain derived from a terminal sialic acid-binding lectin (tsCRD). We produced chimeric virus-like particles MrNV-VLPs to display the tsCRD peptide sequence of the Sambucus Nigra Agglutinin (SNA-I). The tsCRD-MrNV-VLPs maintained their icosahedral structure and increased binding and uptake into ACE2-overexpressing cells. Additionally, these particles exhibited significant blocking capability against various SARS-CoV-2 pseudo-virus variants such as Wuhan, Delta, and Omicron. Our results demonstrated that tsCRD-MrNV-VLPs have the potential to be developed into an effective agent to block and reduce SARS-CoV-2 infection in susceptible cells and present the potential of these VLPs for protective applications.